ANALYSIS OF CHINA’S NATIONAL IMAGE IN ITS INTERNATIONAL COMMUNICATION AND INFLUENCES AS A GLOBAL POWER - Chen Jie, Abdul Muati Ahmad, Sharifah Sofiah Syed Zainudin, Diyana Kasimon (Chelonian Research Foundation, 2023)
The multidimensionality of the national image and the complexity of audience perception have emerged as the real issues facing national image communication with the onset of the worldwide communication era. This essay contrasts cross-cultural empathy communication's theoretical roots and workings with national image communication. It argues that cross-cultural empathy communication, which emphasizes audience characteristics and uses emotional empathy, may represent a breakthrough in the creation of national images. The research defines the national image communication model for cross-cultural empathy. Keywords: communication, international communication, empathic communication, cross-cultural.